2022
DOI: 10.1590/fst.69222
|View full text |Cite
|
Sign up to set email alerts
|

Physiochemical properties and neuroprotective function of Korean major yuzu varieties

Abstract: Three major yuzu varieties, Native, Namhae, and Tadanishiki in Korea were investigated on physiochemical properties and functional characterizations with respect to neuroprotective function (SH-SY5Y cells) or anti-inflammatory (Raw 264.7 cells). Among the three cultivars tested, Namhae had significantly higher fruit weight and total dietary fibers, while Tadanishiki had higher values of both total flavonoid and antioxidant activity. As functional compounds, Tadanishiki contained a 133% of hesperidin and 164% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Numerous studies on phlorotannins have demonstrated their effects on cognitive processes such as learning and memory ( Table 1 ), which are accompanied by changes in neurotransmitter levels such as acetylcholine (ACh), glutamate, γ-aminobutyric acid (GABA), 5-hydroxytryptamine (5-HT), and norepinephrine (NE; Myung et al, 2005 ). In one study, mice exposed to fear-stressed learning were subjected to the Morris water maze test ( Lee and Stein, 2004 ). Mice that consumed brown kelp extract daily for 4 weeks performed significantly better than control mice during the learning and retention phases, suggesting that phlorotannins enhance cognitive resistance to stress.…”
Section: Cognitive Effects Of Phlorotanninsmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies on phlorotannins have demonstrated their effects on cognitive processes such as learning and memory ( Table 1 ), which are accompanied by changes in neurotransmitter levels such as acetylcholine (ACh), glutamate, γ-aminobutyric acid (GABA), 5-hydroxytryptamine (5-HT), and norepinephrine (NE; Myung et al, 2005 ). In one study, mice exposed to fear-stressed learning were subjected to the Morris water maze test ( Lee and Stein, 2004 ). Mice that consumed brown kelp extract daily for 4 weeks performed significantly better than control mice during the learning and retention phases, suggesting that phlorotannins enhance cognitive resistance to stress.…”
Section: Cognitive Effects Of Phlorotanninsmentioning
confidence: 99%
“…Purified PFF-A, eckol, and dieckol were shown to inhibit AChE ( Myung et al, 2005 ; Yoon et al, 2008 ; Kannan et al, 2013 ; Choi et al, 2015 ) and BuChE activity ( Choi et al, 2015 ; Nho et al, 2020 ) in colorimetric enzyme assays. Phlorotannin-rich fractions of brown kelp extract were also shown to inhibit AChE and BuChE activity ( Lee and Stein, 2004 ; Choi et al, 2015 ). It has not yet been determined whether phlorotannins affect ACh levels in vivo using animal models of AD.…”
Section: Effects Of Phlorotannins Against Alzheimer’s Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…It is distinguished from other citrus fruits by having a potent, distinctive aroma and is well-recognized for the delightful fragrance of its outer peel. Yuzu contains high levels of bioactive compounds, such as flavonoids, phenolic compounds, organic acids, and minerals that contribute to its biological activities, including antioxidant, antidiabetic, anti-inflammatory, neuroprotective, anticarcinogenic, and antihypertensive activities ( Kim et al, 2013 ; Lee et al, 2022 , Nam et al, 2021 ). Moreover, yuzu peel is rich in dietary fiber, primarily composed of cellulose, polysaccharides, lignin, and proteins that give their superior physicochemical properties, enhance their biodegradable properties, and contribute to human health benefits as dietetic ingredients ( Lv, Liu, Zhang, & Wang, 2017 ; Karra et al, 2020 , Nam et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%